Investigating the Efficacy of a Canine Rabies Vaccine Following Storage Outside of the Cold-Chain in a Passive Cooling Device - Lugelo, Ahmed; Hampson, Katie; Czupryna, Anna; Bigambo, Machunde; McElhinney, Lorraine M.; Marston, Denise A.; Kazwala, Rudovick; Lankester, Felix (Frontiers in Veterinary Science, 2021)
Thermostable vaccines greatly improved the reach and impact of large-scale programmes to eliminate infectious diseases such as smallpox, polio and rinderpest. A study from 2015 demonstrated that the potency of the Nobivac® Rabies vaccine was not impacted following experimental storage fixed at 30C for three months. Whether the vaccine would remain efficacious following storage under more natural, fluctuating temperature conditions remains unknown. We carried out a randomised controlled non-inferiority trial to compare serological responses in dogs following vaccination with doses stored under cold chain conditions with those stored within a locally made Passive Cooling Device (PCD) under fluctuating temperature conditions. Nobivac® Rabies vaccine was stored under either cold-chain conditions or within the PCD for two months. Daily ambient temperatures and temperatures within the PCD were recorded every three hours. Following storage, 412 domestic dogs were randomly assigned to receive either cold-chain or PCD stored Nobivac® Rabies vaccine. Baseline and day 28-post vaccination blood samples were collected. Serological analysis Fluorescent Antibody Virus Neutralization assay was carried out. A threshold of 0.5 IU/ml was used to determine seroconversion. In addition, the impact of dog body condition score, sex and age on seroconversion was carried out. The serological response of dogs vaccinated using Nobivac® Rabies vaccine stored within the PCD was not inferior to the response of dogs vaccinated using cold-chain stored vaccine (z = 1.1, df = 313, p-value = 0.25). Indeed, the 28-day post vaccination group geometric mean titre was 1.8 IU/ml and 2.0 IU/ml for cold-chain versus non-cold-chain storage, respectively. Moreover, the percentage of dogs that seroconverted in each arm was almost identical (85%). There was a positive linear trend between Body Condition Score (O.R. 2.2, 95% CI: 1.1 – 5.1) and seroconversion, suggesting dogs of poor condition may not respond as expected to vaccination. Our study demonstrated the potency of Nobivac® Rabies vaccine is not impacted following storage under elevated fluctuating temperatures within a PCD. These results have potentially exciting applications for scaling up mass dog vaccination programmes in low-and-middle income countries, particularly for hard-to-reach populations with limited access to power and cold-chain vaccine storage.